Effects of Ability and Effort Praise on Children’s Failure Attribution, Self-Handicapping, and Performance - Xing, Shufen; Gao, Xin; Jiang, Ying; Archer, Marc; Liu, Xia (Frontiers in Psychology, 2018)
Previous research has suggested that children praised for ability are more likely to attribute their failure to low ability compared to those who are praised for effort. At the same time, self-worth theory suggests that when an individual’s self-worth is threatened, they are likely to use a self-serving attributional strategy and self-handicapping. From the perspective of self-worth theory, the present study investigated how ability and effort praise influenced children’s failure attribution, self-handicapping, and their subsequent performance compared to simple informational feedback. Fifth graders (N = 103, average age = 11.2 years, SD = 0.71) were randomly assigned to three praise conditions (ability, effort, or no praise). The results revealed that children praised for ability were more likely to attribute their subsequent failure to non-ability factors and indicate more claimed and behavioral self-handicapping than children who were praised for effort or not praised at all. As behavioral self-handicapping created actual obstacles to progress, children praised for ability made significantly less improvement in their performance than those in the other two groups. In addition, the findings showed that children praised for effort also adopted the claimed self-handicapping and defensive attributional strategies compared to those in the no-praise conditions. These results indicate that parents and teachers should not haphazardly administer praise. Implications for parents, teachers, and future research directions, including the replication of this study in diverse cultural settings, conditions of effort praise, and effects of other types of praise, are discussed.